The Role and Responsibilities of Halal Executives in Food Manufacturing in Malaysia: A Qualitative Study - Nur Shamira Jamil Nasri; Anis Najiha Ahmad; Yumi Zuhanis Has-Yun Hashim; Irshad A. Cader (Universiti Sains Islam Malaysia, 2025)
Indexed by Scopus